Ответ(ы) на вопрос:
Сначала домножим, потом выразим неизвестное:
1) [latex]6*x+22=-5*(x-3)[/latex]
2) [latex]6*x+22=-5*x+15[/latex]
3) [latex]11*x=-7[/latex]
4) [latex]x=-7/11[/latex]
Если скобки не пропущены:
1) [latex](6*x)*(x-3)+22=-5*(x-3)[/latex]
2) [latex](6*x^2-18*x)+22=-5*x+15[/latex]
3) [latex]6*x^2-18*x+22=-5*x+15[/latex]
4) [latex]6x^2-13*x+7=0[/latex]
5) [latex]D=(-13)^2-4*6*7=1[/latex]
6) [latex]x_{1}=(13+1)/12=7/6[/latex]
7) [latex]x_{2}=(13-1)/12=1[/latex]
Не нашли ответ?
Похожие вопросы